STN EN 14067-3: 2004 (28 0340), Železnice. Aerodynamika Časť 3 Aerodynamika v tuneloch - Tomášiková, Eva (Slovenský ústav technickej normalizácie, 2004)
Táto norma je slovenskou verziou EN 14067-3: 2003